Molecular Co-Localization of Human Epstein Barr Virus Infection Associated with the Expressed Protein of Cyclin D1 Dependent Kinase 4 in Hodgkin’s Lymphoma Tissues - Nouri Jaffar Alalsaidissa; Zahraa Ali Abdullah; Ausama Abed-AlkadumAlajeely; Saad Hasan Mohammed Ali; Shakir H Mohammed Al-Alwany (Institute of Medico-legal Publications Pvt Ltd, 2021)
This retrospective case-control study to assess the impact of Cyclin D1 and CDK4 expression along withEBV infection with Hodgkin’s lymphoma (HL).80 lymph node included in this study; (40) formalin-fixed,paraffin- embedded biopsies from Hodgkin’s lymphoma (HL), and (40) apparently healthy lymph nodes ascontrol group. EBV detection was done by CISH whereas IHC detection system was used to evaluate bothCyclin D1 & CDK4 gene expression.The positive –EBERs CISH reactions detected in 16 / 40 (40 %) of Hodgkin lymphoma tissues while positive- EBERs reactions detected in 3 out of 40 tissues (7.5%) in control lymph nodes tissues. Statistically wasfound highly significant between study groups (P value = < 0.05). Cyclin D1 & CDK4 -IHC were detectedin 40% and 52.5% of HL, respectively. Statistically, significant differences noticed among negative, low andmoderate scoring of tissues (P<0.05).Significant EBV gene expressions along with higher percentage of tissues in which Cyclin D1 & CDK4genes being expressed may be indicator their possible role in the pathogenesis and / or the carcinogenesis ofa subset of our Hodgkin’s lymphoma cases.